1996
DOI: 10.1520/jfs14002j
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Quantitation of Source from Hemoglobin of Blood and Blood Mixtures by High Performance Liquid Chromatography

Abstract: The described technique offers a sensitive and reproducible method for inferring the source of over 50 different animal species from bloodstains and blood mixtures. Hemoglobins from each of the species were examined using reversed-phase high performance liquid chromatography (HPLC) in chromatographic times of less than 25 mins. The HPLC method complements and furthers current methodology for identification of species of origin. HPLC analysis is particularly well suited for the quantitative analysis of blood an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…High-performance liquid chromatography (Espinoza, Kirms, & Filipek, 1996;Toorop, Murch, & Ball, 1997), electrophoretic techniques (Ozgen Arun & Ugur, 2000;Renon, Bernardi, Scocca, Cantoni, & Gridavilla, 2003), and enzyme-linked immunosorbent assays (Hajmeer, Cliver, & Provost, 2003;Macedo-Silva et al, 2000) have also been reported. Although most of these protein based methods identified the species-origin of raw meats, they were significantly less sensitive in heat-treated processed meats because of the thermal alteration of the specific epitopes in meat proteins (Hird, Goodier, & Hill, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…High-performance liquid chromatography (Espinoza, Kirms, & Filipek, 1996;Toorop, Murch, & Ball, 1997), electrophoretic techniques (Ozgen Arun & Ugur, 2000;Renon, Bernardi, Scocca, Cantoni, & Gridavilla, 2003), and enzyme-linked immunosorbent assays (Hajmeer, Cliver, & Provost, 2003;Macedo-Silva et al, 2000) have also been reported. Although most of these protein based methods identified the species-origin of raw meats, they were significantly less sensitive in heat-treated processed meats because of the thermal alteration of the specific epitopes in meat proteins (Hird, Goodier, & Hill, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Lipid analysis is only applicable for gross measurement of animal-derived fats (Lumley, 1996;Saeed, Ali, Abdul Rahman, & Sawaya, 1989). Protein-based methods such as high performance liquid chromatography (HPLC) (Espinoza, Kirms, & Filipek, 1996), enzyme-linked immunosorbent assays (ELISA) (Chen & Hsieh, 2000) or isoelectric focusing protein profiles (Skarpeid, Kvaal, & Hildrum, 1998) are effective mainly for unprocessed food and are unable to differentiate species such as lamb and goat or chicken and turkey. Both require complicated procedures and it has proved difficult to accurately quantify the analytes in a short time (Mayer, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The ␣/␤-pair centered at 15112/ 16009 is the coincidental ␣/␤-pair marker for all of these animals. However, HPLC analysis of blood samples from bear, elk, and horse would indicate a difference between the primary structures of the genera's ␣-chains and those of the genera's ␤-chains based upon differing retention times (9). Consequently, HPLC analysis of blood samples from overlapping bear, elk, or horse samples prior to the mass spectrometric analysis should differentiate these species.…”
Section: Resultsmentioning
confidence: 99%